Inter- and intrahemispheric EEG coherence and visuomotor performance during shooting competition and practice - Woo, M.; Kim, Y. (Perceptual and Motor Skills, 2017)
This study compared inter- and intrahemispheric cortical networking and visuomotor performance during practice and competition in 14 air pistol athletes (mean age of 17.8 years). Participants self-reported their competitiveness, stress, confidence, and relaxation through visual analog scales; shooting score and aiming time were measured by the SCATT program. Inter- and intrahemispheric coherences during aiming were analyzed. Under competition following the practice condition, self-reported competitiveness and stress were higher, but confidence was lower. Aiming time during competition was longer than during practice; but there were no significant shooting score differences between conditions, perhaps due to only low-grade competitive anxiety. Through coherence analysis, interhemispheric coherence during aiming was higher under competition, relative to practice. Competitive anxiety seems to result in reduced neural efficiency and regional cortical autonomy, though there was no intrahemispheric electroencephalogram coherence difference between competition and practice conditions.